JURIDICIAL REVIEW OF DISASTER RESPONSE DISPUTES IN THE PUBLISHING AGREEMENT FOR COLLEGE OF - Herlambang, Dian (Progressive Law Review, 2019)
Darmajaya Press as one of the publications in Bandar Lampung which is also a part of university publishing. Settlement of copyright disputes is very necessary to know and do to analyze how to resolve copyright disputes both in terms of moral rights and economic rights and also to answer the application of copyright that occurs in the Darmajaya Press publisher. This type of research is normative legal research. This type of research examines the implementation of positive legal provisions, agreements, contracts factually in legal events that occur. This type of research is descriptive in that this study has the aim to explain clearly and in detail in the legal events that occur. The results of the study indicate that the cooperation agreement between CV. Aura Publishing with IIB Darmajaya there has been a clause on the settlement of copyright disputes which is feared that it will arise in the future, namely by implementing a form of dispute resolution, namely alternative dispute resolution and courts; The application of copyright is carried out through the desire of Darmajaya Press to become a member of IKAPI, and in the agreement made there is a clause must reach 10 book publications, so that currently only 7 titles of ISBN books have been reached. Then the writer (lecturer) who published the book had not made a publishing agreement to guarantee copyright both moral rights and economic rights owned by the author.